Opportunities And Challenges Of Islamic Banking In Indonesia In The Digital Era - Choirunnisak Nisa; Mohamad Irsyad; Shofia Mauizotun Hasanah (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to identify the opportunities and challenges faced by Islamic banking in the digital era and to formulate strategic steps for its development. The digital transformation characterized by the emergence of technologies such as artificial intelligence (AI), blockchain, the Internet of Things (IoT), and big data has revolutionized the global financial system, including the Islamic banking industry. Using a library research approach, data were collected from various scientific literatures such as journals, books, and official reports related to digital Islamic economics and finance. The findings indicate that digitalization presents significant opportunities for Islamic banking to enhance operational efficiency, expand financial inclusion, and foster innovation in products based on Sharia principles—such as mobile banking, halal e-wallets, and Sharia-based crowdfunding platforms. Nevertheless, several challenges persist, including limited Sharia digital literacy, cybersecurity threats, insufficiently skilled human resources (HR) in both technology and Sharia disciplines, and the need for adaptive digital regulations and fatwas. To address these issues, this research recommends several strategic steps: developing a digital transformation roadmap, strengthening infrastructure and cybersecurity, improving digital literacy, developing Sharia digital human resources, fostering collaboration between Islamic banks and fintech, and harmonizing regulations and fatwas with technological developments. The study concludes that the success of digital transformation in Islamic banking largely depends on the synergy between technology, Sharia principles, and strong regulatory support, in order to realize an inclusive, efficient, and sustainable Islamic financial system in the digital age.